Effects of acetic acid and povidone iodine dressings as modulators of local environment in chronic wounds as synergists and separate agents - Syed, Tausif Kamal; Apturkar, D. K.; Dandekar, K. N.; Baviskar, P. K.; Jorwekar, G. J.; Shaikh, Meena H. (International Surgery Journal, 2021)
Background: Wound care management has long been a primary point of care for surgeons and clinicians alike. The burden of care and time required in the management of wounds has led to development of innovative and expensive materials which alleviate the burden of healing on our physiology and reinforce the healing mechanisms. Methods: A case series analysis of 240 patients included on accrual was carried out. These patients were randomly assigned to 3 groups. Group A ulcers were dressed with 2% acetic acid soaked sterile pads. Group B received the acetic acid-iodine combination and group C dressed with traditional Povidone-Iodine ointment and solution. These ulcers were evaluated on admission and on intervals of 5 days with a customized scoring system, Dr. Kamal’s adaptive wound healing score (KAWHS). A sterile culture swab with coverage of healthy granulation tissue was considered the primary end point of the study. Results: Resolution of slough was significantly earlier in group A and B as compared to group C. odor subsided earliest in group A, followed by group B and C. Resolution of purulent discharge was achieved earliest in Group B which was significant in comparison to group A and C. Wound healing was observed to be better in acetic acid usage groups. Conclusions: Acetic acid dressings are effective in treating chronic non-healing wounds with mono and poly-microbial culture.